Implementation of the Independent Curriculum in Madrasah Ibtidaiyah - Suciningsih,; Ningsih, Tutuk; Mawardi, Kholid; Zainol, Nur Zainatul Nadra (Advances in Humanities and Contemporary Studies, 2024)
Curriculum changes require time for adjustment and strong support from madrasa management and require assistance from related parties so that teachers are able to pass through the transition period successfully. The implementation of the Independent Curriculum (IKM) at Madrasah Ibtidaiyah (MI) will begin to be implemented in its entirety in grades I and IV for the 2023/2024 academic year. This is in accordance with the Minister of Education and Culture's decision number 1443 of 2023 concerning Madrasas Implementing the Independent Curriculum for the 2023/2024 Academic Year. A new era has begun, and teachers are not ready to face curriculum changes for several reasons, including the absence of special training regarding the independent curriculum, technical guidance for the online independent curriculum which is followed independently by teachers is ineffective, as well as constraints on teacher resources in terms of information technology. Some of these things make teachers not ready in mindset to face curriculum changes. Even this change in the curriculum has created feelings of uncertainty and anxiety for teachers. To overcome this, the efforts made by the Madrasah Ibtidaiyah (MI) Teacher Working Group (KKG) include holding Technical Guidance (BIMTEK) activities for the Implementation of the Independent Curriculum (IKM) for teachers by bringing in communicative and professional resource persons. The aim of this research is to analyze the readiness of teachers' mindsets after the implementation of technical guidance on the implementation of the independent curriculum which was carried out for two days at the Ibtidaiyah madrasah. The efforts made by the Madrasah Ibtidaiyah (MI) Teacher Working Group (KKG) include holding Technical Guidance (BIMTEK) activities for the Implementation of the Independent Curriculum (IKM) for teachers by bringing in communicative and professional resource persons. The aim of this research is to analyze the readiness of teachers' mindsets after the implementation of technical guidance on the implementation of the independent curriculum which was carried out for two days at the Ibtidaiyah madrasah. The efforts made by the Madrasah Ibtidaiyah (MI) Teacher Working Group (KKG) include holding Technical Guidance (BIMTEK) activities for the Implementation of the Independent Curriculum (IKM) for teachers by bringing in communicative and professional resource persons. The aim of this research is to analyze the readiness of teachers' mindsets after the implementation of technical guidance on the implementation of the independent curriculum which was carried out for two days at the Ibtidaiyah madrasah..The research methods used in this research were a questionnaire of 27 teachers and interviews with the head of the madrasah ibtidaiyah teacher working group. This research on the Implementation of the Independent Curriculum in Madrasah Ibtidaiyah will provide a valuable contribution to the development of education at the Madrasah Ibtidaiyah level